SINTESIS DAN KARAKTERISASI PARTIKEL NANOSPERIK TIO2 MELALUI METODE HIDROTERMAL GELOMBANG MIKRO - Amir, Amelia; -, Emriadi; Arief, Syukri; Manseki, Kazuhiro; Sugiura, Takashi (Universitas Andalas, 2014)
Â ABSTRACTSimple synthesis of nanospherical TiO2 by microwave hydrothermal method has beeninvestigated. Titanium tetra isopropoxide (TTIP) and tetra methyl ammonium hydroxide(TMAOH) were used as precursor. The crystal phase and microstructure were characterized byX-Ray Diffraction (XRD) and transmission electron microscopy (TEM) including selected areadiffraction (SAED). The presence of intense peak in the XRD patterns confirmed to anatase andin good agreement with SAED patterns. Nanospherical of particles were clearly seen in theTEM image and the size of particles was approximately 4-5 nm.Keywords : microwave hydrothermal, colloidal titanates, structure directing agent,nanospherical TiO2